The lost bookshop - Woods, Evie (London : One More Chapter, 2023)
On a quiet street in Dublin, a lost bookshop is waiting to be found... For too long, Opaline, Martha and Henry have been the side characters in their own lives. But when a vanishing bookshop casts its spell, these three unsuspecting strangers will discover that their own stories are every bit as extraordinary as the ones found in the pages of their beloved books. And by unlocking the secrets of the shelves, they find themselves transported to a world of wonder... where nothing is as it seems.
First published in Great Britain in ebook format by Harper Collins Publishers.
Keywords: Bookstores -- Fiction; Imaginary places -- Fiction; Romance fiction; Dublin (Ireland) -- Fiction; Romance fiction